The Importance of the Spiritual Dimension in Improving the Mental Well-Being of College Students - Milatun Nadifa; M Baihaqi Rizki Abdul Latif; Ahmad Yusuf Sobr; Aan Fardani Ubaidillah (Studies in Learning and Teaching, 2024)
The research investigated the relationship between spirituality and students' mental well-being. The aim was to explore the impact of high spiritual levels on different aspects of mental well-being through the results of previous research. This research uses the Systematic Literature Review (SLR) method, which includes the identification, review, evaluation, and interpretation of various existing studies. The findings suggest a strong link between high spiritual levels and improved mental well-being among college students. Students with high spirituality showed higher levels of purpose, gratitude, effective stress management, positive social relationships, and better physical health. The research contributes new insights by highlighting the significant impact of spirituality on diverse aspects of mental well-being in the context of university life and college efforts to deal with it. These findings underscore the importance of integrating the spiritual dimension into mental health and Education programs and provide a foundation for future studies to explore specific spiritual practices and cultural variations in more detail that can be applied practically to higher education. Some of the efforts that universities can make are providing materials about spirituality in the curriculum, providing affordable mental health services, creating a conducive learning environment, and providing social support to students. Some programs that can be done by universities include religious activities, meditation or yoga activities, and volunteer activities. These refinements add a novelty aspect to the research by emphasizing its practical implications. As such, the research not only presents findings on the relationship between spirituality and students' mental well-being but also highlights their relevance in the context of higher education policy and practice.